Influence of Harvesting Date on Chemical Maturity for Processing Quality of Potatoes - Sharkar, M; Ahmed, JU; Hoque, MA; Mohi-Ud-Din, M (Annals of Bangladesh Agriculture, 2019)
The present study was conducted to find out a suitable harvesting date of processing potato varieties (Asterix, Courage and Lady Rosetta) from three different harvest dates [80, 90, and 100 days after planting (DAP) harvest] by chemical maturity monitoring. Eighty DAP harvest resulted the lowest mean total soluble sugar (TSS) (3.77 mg/g FW), reducing sugar (RS) (1.57 mg/g FW), sucrose (2.40 mg g-1 FW), fructose (0.77 mg/g FW) and polyphenol (238.94 μg/g FW) contents in all the varieties and at the same DAP harvest, dry matter (DM) content (21.71%) and chip color index (CCI) (0.67) remained at the lowest. Tubers harvested at 80 DAP produced good quality and acceptable colored processed products as it meets up the required processing quality, but lesser DM content might increase the cost of the product. Optimum DM content (24.07%) with moderate level of different sugar contents and acceptable CCI (1.13 to 1.85, <2.00) was found at 90 DAP harvest. Therefore, 90 DAP harvest could be considered as suitable harvesting date for processing by compromising some quality parameters (TSS, RS, sucrose, fructose and polyphenol contents). Among the varieties, Lady Rosetta and Courage were preferable for producing quality potato products. Highly significant and positive correlation existed between CCI and different chemical parameters. A strong correlation coefficient (r = 0.822**) and good fit (R2 = 0.6755) of the regression equation (CCI = 0.9341RS – 0.4969) between CCI and RS indicated that RS content played the vital role in the browning of the processed potato products. Ann. Bangladesh Agric. (2019) 23(2) : 89-103